The Link Between Cannabis Use and Violent Behavior in the Early Phase of Psychosis: The Potential Role of Impulsivity - Moulin, Valerie; Framorando, David; Gasser, Jacques; Dan-Glauser, Elise (Frontiers in Psychiatry, 2022)
Recently, the literature has shown that Cannabis Use (CU) was a risk factor for Violent Behavior (VB) in patients with psychosis, and particularly those in the early phase of psychosis (EPP). These findings are relevant because of the high prevalence of CU in this phase of psychosis, and the potential for prevention during this early phase of illness. However, there is still a lack of clear explanations, supported by empirical evidence, about what underlies the link between CU and VB against other. Method. This viewpoint reviews the scientific literature on the link between CU and VB, and the involvement of impulsivity in this relationship. This last point will be addressed at the clinical and neurobiological levels. Results. Recent studies have confirmed that CU is particularly high in the EPP, and that CU is a major risk factor for VB in the EPP and schizophrenia. Studies have also shown that impulsivity is a risk factor for VB in psychosis, is associated with CU, and that may mediate the link between CU and VB. Evidence points toward a neurobiological mechanism, since CU affects structures and functioning of frontal areas that are known to play a major role in impulsive behavior. Conclusion. Scientific data support the involvement of impulsivity as a variable that could mediate the link between CU and aggression, and, in particular, when CU has an early onset. Evidence highlights the relevance of early behavioral prevention in the EPP by targeting impulsivity and CU in addition to interventions focusing psychotic disorders.